ANALISIS PELAKSANAAN PENGAYAAN PADA PESERTA DIDIK MATA PELAJARAN IPA DI SMP NEGERI 2 TARAKAN - Sesa Sesa; Fitri Wijarini; Zulfadli Zulfadli (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2022)
The purpose of this study was to analize the implementation of enrichment in science subjects at SMP Negeri 2 Tarakan. This research is a case study research with a qualitative approach. The data collection used in this study were interviews, observation, and documentation. The data were analyzed using data reduction, data presentation, conclusion drawing, and data triangulation to help analyze and check the data's validity. The objects in this study were theree science teachers in class VII, VIII, and IX and the subjects in this study were the Principal of SMP Negeri 2 Tarakan, the Deputy Principal of Curriculum of SMP Negeri 2 Tarakan, and three students. Based on data analysis conducted, the results of the study showed that there was one teacher who carried out enrichment while the other two teachers did not carry out enrichment. The implementation of enrichment such as independent study, giving project assignments, and providing additional material. The obstacles to the implementation of enrichment were time limits to conduct enrichment, the ability or learning outcomes of students, and differences in student characteristics.